Serum amyloid A protein as a predictor of severity in coronavirus disease 2019-infected Egyptian patients - Dalia A.E.M.A.E.R. Negm; Wafaa M.A.E.-W. Elzefzafy; Sabah E.A. El Raheem; Nessren M.B. El Deen (Wolters Kluwer Medknow Publications, 2023)
Background The coronavirus disease 2019 (COVID-19) pandemic is a worldwide pandemic of COVID-19 caused by severe acute respiratory syndrome coronavirus. Serum amyloid A (SAA) is an acute-phase protein secreted during the acute phase of inflammation and can be used to predict the severity of COVID-19 disease. When inflammatory stimuli occur, levels of SAA increase within hours and the magnitude of response becomes great and may be greater than that of C-reactive protein (CRP). Aim Assessment of the level of SAA in COVID-19 Egyptian patients to predict the severity of the disease. Patients and methods This was an observational case-control study conducted on 80 participants: 60 patients with RT-PCR positive and computed tomography chest for COVID-19 disease classified into three groups according to disease severity: group I (20 patients) mild cases, group II (20 patients) moderate cases, and group III (20 patients) severe cases, and 20 participants as a control group. All participants were investigated for complete blood count, Serum Glutamic Pyruvic Transaminase (SGPT), Serum Glutamic Oxaloacetic Transaminase (SGOT), blood urea, serum creatinine, CRP, D-dimer and SAA. Results There is no statistical significance among the comparison groups as regards SAA. There was a high statistically significant decrease in the number of lymphocytes in COVID-19 patient groups compared with the control group. There was a statistically significant difference as regards platelet count, CRP, D-dimer, serum urea, and creatinine among the groups (I, II, and III) compared with the control group. Conclusion Single use of SAA during the pandemic could not achieve prediction of severity or the prognosis of COVID-19.